2007
DOI: 10.1302/0301-620x.89b2.17747
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxibversusibuprofen in the prevention of heterotopic ossification following total hip replacement

Abstract: We examined whether a selective cyclooxygenase-2 (COX-2) inhibitor (celecoxib) was as effective as a non-selective inhibitor (ibuprofen) for the prevention of heterotopic ossification following total hip replacement. A total of 250 patients were randomised to receive celecoxib (200 mg b/d) or ibuprofen (400 mg t.d.s) for ten days after surgery. Anteroposterior radiographs of the pelvis were examined for heterotopic ossification three months after surgery. Of the 250 patients, 240 were available for assessment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 30 publications
1
44
0
6
Order By: Relevance
“…In general, with the exception of aspirin, most NSAIDs used in medium-to-high dosage regimens showed an approximate relative reduction in postoperative heterotopic ossification of 57% [20]. Recently, selective cycloxygenase-2 (COX-2) inhibitors were shown to be more effective in the prevention of formation of ectopic bone than ibuprofen [23]. These results, in addition to the reduced gastrointestinal side effects, suggest that, after excision of ectopic bone formation, a short period of prophylaxis with COX-2 inhibitors may be the preferred treatment for prevention of recurrence of heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
“…In general, with the exception of aspirin, most NSAIDs used in medium-to-high dosage regimens showed an approximate relative reduction in postoperative heterotopic ossification of 57% [20]. Recently, selective cycloxygenase-2 (COX-2) inhibitors were shown to be more effective in the prevention of formation of ectopic bone than ibuprofen [23]. These results, in addition to the reduced gastrointestinal side effects, suggest that, after excision of ectopic bone formation, a short period of prophylaxis with COX-2 inhibitors may be the preferred treatment for prevention of recurrence of heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantages include a reduced side-effect profile and less intra-and postoperative bleeding [6]. Studies so far have demonstrated reduced incidence of gastrointestinal bleeding [7]. More recently, concerns have been expressed over potential cardiovascular complications, with increased risk of myocardial infarction with the use of selective COX-2 inhibitors [8].…”
Section: Selective Cox-2 Inhibitorsmentioning
confidence: 99%
“…More recently, concerns have been expressed over potential cardiovascular complications, with increased risk of myocardial infarction with the use of selective COX-2 inhibitors [8]. Recent publications lend weight to current established literature suggesting that COX-2 inhibitors are efficacious in the prophylaxis of HO [7,9]. There is still, however, a lack of evidence to support selective COX-2 inhibitors as a firstline treatment over indomethacin for the treatment of HO.…”
Section: Selective Cox-2 Inhibitorsmentioning
confidence: 99%
“…[71]. В исследование включено 250 больных, перенес-ших эндопротезирование тазобедренного сустава, которые для профилактики ГО в течение 10 дней после операции по-лучали целекоксиб 200 мг 2 раза в день или ибупрофен по 400 мг 3 раза в день.…”
Section: субхондральная кость Nf-кв/rankl-зависимая активизация остеоunclassified